2012
DOI: 10.1097/acm.0b013e318248e9d0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Medical Student Personality and Health/Wellness Characteristics With Their Medical School Performance Across the Curriculum

Abstract: This study identified two sets of skills (cognitive, noncognitive) used during medical school, with minimal overlap across the types of performance (e.g., exam performance versus clinical interpersonal skills) they predict. Medical school admission and evaluation efforts may need to be modified to reflect the importance of personality and other noncognitive factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 62 publications
(48 reference statements)
4
71
0
4
Order By: Relevance
“…1 The direction of the association has been contextually dependent with introverted students having higher academic success in the 1st year, 2 lower evaluations related to interpersonal behavior in clerkship years, 3 and higher stress levels overall than their extraverted peers. 4,5 Although these studies inform us that introverted and extraverted medical students perform and respond differently, we know little about the learning environment's influence on introverted students' thoughts, emotions, actions, or well-being.…”
Section: Introductionmentioning
confidence: 98%
“…1 The direction of the association has been contextually dependent with introverted students having higher academic success in the 1st year, 2 lower evaluations related to interpersonal behavior in clerkship years, 3 and higher stress levels overall than their extraverted peers. 4,5 Although these studies inform us that introverted and extraverted medical students perform and respond differently, we know little about the learning environment's influence on introverted students' thoughts, emotions, actions, or well-being.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] Their overall psychological distress is consistently higher than in the general population and may impact on their academic performance. [5,6] Stress may foster anxiety, substance abuse, burnouts leading to abandonment of studies, depression, and even suicidal ideation. [3,7,8] There are many possible stressors to which medical students may be exposed.…”
Section: Introductionmentioning
confidence: 99%
“…In their metaanalytic research, Barrick and Mount (1991) concluded that conscientiousness is a universal predictor of job performance. The universality of the Conscientiousness factor in academic and professional success has been confirmed in a variety of disciplines and in different academic settings (Hurtz & Donovan 2000;Noftle & Robins 2007;Poropat 2009;Haight et al 2012), and in predicting healthy behavior (Bogg & Roberts 2004). Thus, conscientiousness is the first personality attribute we selected as being relevant to medical education and the practice of medicine.…”
Section: Selected Personality Measuresmentioning
confidence: 99%
“…For example, the ability to recall, compartmentalize and organize factual information, as well as test-taking skills, under the rubric of ''cognitive'' abilities, often contribute to success in the preclinical phase. However, communication and interpersonal skills, bedside manner, Personality assessments in medical education attitudes, personal qualities or characteristic (referred to as ''noncognitive'' attributes), often contribute to the assessments of competence in the clinical phase (Haight et al 2012).…”
Section: Validity Concernsmentioning
confidence: 99%